Students’ Learning Styles and Their Speaking Proficiency: Evidence from MAN 1 Makassar - L, Sulfitriani; Korompot, Chairil Anwar; Sakkir, Geminastiti (Yayasan Cendekiawan Indonesia Timur, 2025)
This study investigates how different learning styles—visual, auditory, and kinesthetic—influence students’ English-speaking performance. Speaking is widely recognized as the most challenging language skill, and students’ preferred modes of learning are believed to shape how effectively they develop oral proficiency. Using a descriptive quantitative design, data were collected from eleventh-grade students at MAN 1 Makassar through a learning style questionnaire adapted from the VAK model and a speaking performance test assessed using Heaton’s criteria of accuracy, fluency, and comprehensibility. The results reveal clear performance differences across learning style categories. Auditory learners achieved the highest mean score, classified as Very Good, demonstrating strong fluency and clear comprehensibility with only minor pronunciation or grammatical issues. Visual learners obtained a Good classification; they performed well overall but showed noticeable limitations in grammatical accuracy. Kinesthetic learners received a Fairly Good classification, exhibiting moderate ability and particular challenges in fluency, as their speech tended to be fragmented and required more processing time. These findings indicate that students' learning styles are meaningfully associated with their speaking performance, with auditory learners showing the greatest advantage—likely due to their preference for processing spoken input and verbal explanations. Meanwhile, kinesthetic learners may require more interactive, movement-based activities to support their oral production. The study underscores the importance of incorporating varied instructional strategies that align with different learning preferences. Teachers are encouraged to design multimodal speaking activities to ensure equitable support for all learner types and to maximize students’ opportunities for successful oral communication.